Correlation between pathologic complete response, event-free survival/disease-free survival and overall survival in neoadjuvant and/or adjuvant HR+/HER2-breast cancer - Gogate, Anagha; Ranjan, Sandip; Kumar, Amit; Bhandari, Hitesh; Papademetriou, Eros; Kim, Inkyu; Potluri, Ravi (Frontiers in Oncology, 2023)
Purpose: The study’s purpose was to evaluate the correlation between overall survival (OS) and its potential surrogate endpoints: pathologic complete response (pCR) and event-free survival (EFS)/disease-free survival (DFS) in neoadjuvant and/or adjuvant HR+/HER2- breast cancer. Methods: Systematic search was performed in MEDLINE, EMBASE, Cochrane Library databases and other relevant sources to identify literature that have reported outcomes of interest in the target setting. The strength of correlation of EFS/DFS with OS, pCR with OS, and pCR with EFS/DFS was measured using Pearson's correlation coefficient (r) based on weighted regression analysis. For Surrogate Endpoint-True Endpoint pairs where correlation was found to be moderate, surrogate threshold effect (STE) was estimated using a mixed-effects model. Sensitivity analyses were conducted on the scale and weights used and removing outlier data. Results: Moderate correlation was observed of relative measures [log(HR)] of EFS/DFS and OS (r = 0.91; 95% CI: 0.83, 0.96, p < 0.0001). STE for HREFS/DFS was estimated to be 0.73. Association between EFS/DFS at 1, 2 and 3 years with OS at 4- and 5-year landmarks was moderate. Relative treatment effects of pCR and EFS/DFS were not strongly associated (r: 0.24; 95% CI: -0.63, 0.84, p = 0.6028). Correlation between pCR and OS was either not evaluated due to inadequate sample size (relative outcomes) or weak (absolute outcomes). Results obtained in the sensitivity analyses were similar to base scenario. Conclusions: EFS/DFS were moderately correlated with OS in this trial-level analysis. They may be considered as valid surrogates for OS in HR+/HER2- breast cancer.